2015
DOI: 10.1089/acu.2015.1154
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Pediatric Conditions: A Narrative Review

Abstract: Background: The use of acupuncture for common pediatric conditions continues to grow. Three previous overviews have summarized the research literature. Objective: The aim of this article is to provide an updated narrative review of the literature on the use of acupuncture within the pediatric population. Methods: A systematic search was performed to identify clinical trials and reviews published through July 2015. Trials were excluded if they were not: (1) acupuncture-specific; (2) limited to pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The efficacy of acupuncture for some diseases is promising and there have been no fatal side effects reported in children. 48 Furthermore, three recent reviews and some trials have suggested that acupuncture is a safe therapy in preterm and term neonates, in infants and in children. 21,4952 However, safety aspects were poorly reported in the reviewed trials.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of acupuncture for some diseases is promising and there have been no fatal side effects reported in children. 48 Furthermore, three recent reviews and some trials have suggested that acupuncture is a safe therapy in preterm and term neonates, in infants and in children. 21,4952 However, safety aspects were poorly reported in the reviewed trials.…”
Section: Discussionmentioning
confidence: 99%
“…Paul Nogier, MD, a French doctor, first introduced this therapy to the world in Marseille, in 1957, 1 earning ear acupuncture recognition in its present form. 1,2 Although in the past, acupuncture treatment of children did not seem to play a major role in Traditional Chinese Medicine (TCM), 3 interest in complementary and integrative therapies for children has been increasing 4,5 in the last few years. TCM includes (1) massage therapy (known as Tu'ina), (2) moxibustion, and (3) different kinds of acupuncture and acupressure.…”
Section: Introductionmentioning
confidence: 99%